PENERAPAN METODE HEURISTIC EVALUATION UNTUK ANALISA USABILITY PADA APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL - Wahyuni, Asri; Suhas, Marhiz (Jurnal Informatika, 2024)
Dukcapil to meet the need for community population data to a smartphone to build IKD (Digital Population Identity). Digital Population Identity (IKD) is electronic information that is usually used to represent population documents, feedback data, in a digital application based on a smartphone that displays data as the identity in question. However, from user assessments obtained through Playstore, several problems were found, such as the fact that the document resolution was low so that the resulting display was less clear and less comfortable to read, the document download function was not yet available, some documents often failed to display, and when logging out or uninstalling the application is difficult to log in again. Based on this problem, an evaluation performed using the HE method (Heuristic Evaluation). This method was chosen to test the Digital Population Identity program to find usability problems in the Digital Population Identity application which is based on 10 heuristic method principles so that improvements can be obtained. To test the statements in the questionnaire, researchers used validity tests and reliability tests. Determining the priority scale for application improvements using severity rating using the index calculated from the Heuristic evaluation. This research resulted in a usability analysze IKD application using the HE method (heurisctic evaluation), that of the level of usability of IKD program had  Cronbach's Alpha  0.973 from 27 statements, which means that the reliability IKD application is very reliable. Recommendations for improving the Digital Population Identity application for problem codes PM23 and PM27 can used as a reference improving this program so it can meet user needs.